Match each quadratic function given in factored form

with its equivalent standard form listed on the left.

-f(*) = (x + 2)(x – 6)

f(x) = (x – 4)(x + 3)

f(x) = (x – 12)(x 1)

f(x) = (x -3)(x + 4)

with its equivalent standard form listed on the left.

-f(*) = (x + 2)(x – 6)

f(x) = (x – 4)(x + 3)

f(x) = (x – 12)(x 1)

f(x) = (x -3)(x + 4)

Answer:Step-by-step explanation:standardform of the givenquadratic equationin factored form iswhat are quadratic equations?To convert a factored quadratic function into the standard form, we first need to open the brackets by multiplying the integers. Then carry out addition or subtraction operations to obtain the equation.standard formof equations 2,3 and 4 are :quadratic functionhere: